PEMANFAATAN SPENT BLEACHING EARTH (SBE) YANG TELAH DIEKSTRAKSI SEBAGAI BAHAN CAMPURAN PEMBUATAN BATU BATA DENGAN VARIASI 0%, 30%, 40%, 50%, dan 60%. - Kelvin Ananda; Fakhri; Azhari; Andre Novan; Ermiyati (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2025)
This study aims to utilize extracted Spent Bleaching Earth (SBE) waste as an additive material in the production of clay bricks. SBE waste is a by-product of the palm oil bleaching process, which is abundantly available and has the potential to cause environmental pollution if not properly managed. The variations of SBE content used in this research were 0%, 30%, 40%, 50%, and 60% of the total clay weight. Tests were conducted on the physical appearance, dimensions, porosity, and compressive strength of the resulting bricks. The results showed that the addition of SBE waste affected the color and surface texture of the bricks, where higher SBE content tended to decrease visual quality. The volume shrinkage values ranged from 35.24% to 39.34%, which still met the requirements of SNI 15-2094-2000. However, the compressive strength test results indicated a decrease as the SBE percentage increased, with the highest value of 2.70 MPa and the lowest of 1.76 MPa, both below the minimum SNI standard of 5 MPa (Class III). Overall, SBE waste can be utilized up to a 30% variation as an alternative additive material in brick production, but further optimization is required by reducing the mixture variation to meet the structural strength standards.